Integration models for indigenous public health curricula. Issue 4 (7th June 2017) - Coombe, Leanne; Lee, Vanessa; Robinson, Priscilla
ABSTRACT: All graduates of Master of Public Health (MPH) programmes in Australia are expected to achieve a core set of Indigenous public health competencies designed to train 'judgement safe practitioners'. A curriculum framework document was developed alongside the competencies to assist programme providers to integrate appropriate Indigenous content, but it does not describe the intended integration model. A review of MPH programmes was undertaken to determine the extent of integration, identify examples of best practice and explore how integration can be improved. Data from the consolidated review findings were analysed using a staged approach. Several models of curricula integration were identified, building on known models, and definitions developed that differentiate features according to the extent of integration achieved. The model recommended in the literature as best practice, known to promote deep learning, was found in only one of the reviewed programmes. This combination model supports development of reflexive practitioners who can operate across different disciplines and ways of knowing. Enablers and barriers were explored to explain why some integration models were more commonly found. Implications for curriculum reform are outlined with strategies to assist implementation of a combined integration model, a necessary learning approach to enhance student cultural competence.